Acinetobacter Infections and Outcomes at an Academic Medical Center: A Disease of Long-Term Care. (12th March 2015) - Townsend, Jennifer; Park, An Na; Gander, Rita; Orr, Kathleen; Arocha, Doramarie; Zhang, Song; Greenberg, David E.
Abstract: Background.  Our study aims to describe the epidemiology, microbial resistance patterns, and clinical outcomes of Acinetobacter infections at an academic university hospital. This retrospective study analyzed all inpatient clinical isolates of Acinetobacter collected at an academic medical center over 4 years. The data were obtained from an Academic tertiary referral center between January 2008 and December 2011. All consecutive inpatients during the study period who had a clinical culture positive for Acinetobacter were included in the study. Patients without medical records available for review or less than 18 years of age were excluded. Methods.  Records were reviewed to determine source of isolation, risk factors for acquisition, drug resistance patterns, and clinical outcomes. Repetitive sequence-based polymerase chain reaction of selected banked isolates was used to determine patterns of clonal spread in and among institutions during periods of higher infection rates. Results.  Four hundred eighty-seven clinical isolates of Acinetobacter were found in 212 patients (in 252 admissions). Patients with Acinetobacter infections were frequently admitted from healthcare facilities (HCFs) (59%). One hundred eighty-three of 248 (76%) initial isolates tested were resistant to meropenem. One hundred ninety-eight of 249 (79.5%) initial isolates were multidrug resistant (MDR). Factors associated with mortality included bacteremia (odds ratio [OR] = 1.93, P = .024), concomitant steroid use (OR = 2.87, P < .001), admission from a HCF (OR = 6.34, P = .004), and chronic obstructive pulmonary disease (OR = 3.17, P < .001). Conclusions.   Acinetobacter isolates at our institution are frequently MDR and are more common among those who reside in HCFs. Our findings underline the need for new strategies to prevent and treat this pathogen, including stewardship efforts in long-term care settings.